Counteracting Bullying in Higher Education Institutions Against People with Disabilities (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the topical issue of counteracting bullying in higher education institutions against people with disabilities. With the active implementation of inclusive education in Ukraine, the issue of ensuring a safe educational environment for students with disabilities is becoming particularly relevant. Despite the existence of regulatory and legal acts and state support programmes, this category of students remains vulnerable to discrimination and psychological violence, which is exacerbated by the state of martial law.The aim of the study is to analyse the psychological characteristics of bullying in the student environment and to identify effective ways of preventing it, using the example of the Open International University of Human Development “Ukraine”. The research analysed scientific literature, identified methodological tools, conducted empirical research, and developed practical recommendations for the prevention of bullying.The author's concept is based on the idea of creating a safe, accessible, and supportive educational environment for students with disabilities. It has been established that manifestations of bullying against persons with disabilities have their own specific features – verbal abuse, social exclusion, cyberbullying. The issue of bullying in higher education institutions with regard to this category of students remains insufficiently researched, which necessitates the improvement of preventive measures.The empirical part of the study included questionnaires, projective techniques, and diagnosis of aggression among students with disabilities aged 18 to 19. The results showed that 12.9 % of the students surveyed had experienced bullying in higher education institutions, and 61.3 % had experienced humiliation throughout their lives. The most common forms of bullying were verbal abuse and harassment on social media. The study also revealed the low effectiveness of adults’ responses to bullying. Based on the results of the study, ways to prevent bullying in higher education institutions were proposed: raising awareness of students and teachers about the problem of bullying, developing adapted procedures for responding to its manifestations, and introducing training aimed at developing empathy, tolerance, and social responsibility. The need for further theoretical and applied research is emphasised in order to gain a deeper understanding of the problem and develop comprehensive support programmes for students with disabilities in the educational environment.